Epidemiologia da Rickettsia parkeri cepa Mata Atlântica no Estado do Espírito Santo, Brasil - Martinez, Alvaro Adolfo Faccini (2020)
Since 2010, a new rickettsiosis caused by Rickettsia parkeri, a species included in the spotted fever group (SFG) and transmitted by the tick Amblyomma ovale, has been described in Brazil. Considering that A. ovale does occur in the Espírito Santo state (ES), the present study aimed at preliminarily describing the epidemiology of R. parkeri in the Atlantic forest of this state. Between June 2016 and September 2018, 33 villages from nine municipalities of the ES were included in a study for the molecular detection and isolation of SFG rickettsiae from adult Amblyomma ticks collected on dogs with free access to the forest. Serologic screenings against SFG rickettsiae in these animals and their owners (humans) were performed through immunofluorescence assay (IFA) using antigens of Rickettsia rickettsii and R. parkeri. Additionally, local health secretariats were informed on clinical manifestations of R. parkeri infection and told to communicate any suspected case. A total of 280 adult ticks were collected and taxonomically classified as A. ovale (n=152), Amblyomma aureolatum (n=127) and Amblyomma sculptum (n=1). Overall, Rickettsia DNA was detected in 12/266 ticks. The sequencing of PCR products revealed that 0.7% (1/144) and 0.8% (1/121) of the analyzed A. ovale and A. aureolatum ticks were infected by R. parkeri strain Atlantic rainforest, respectively, and 8.3% (10/121) of the A. aureolatum ticks infected by Rickettsia bellii. Among the above PCR-positive ticks, only one isolate from one A. aureolatum tick was successfully established in the laboratory. DNA extracted from the third passage of this isolate was designated as strain M9A and molecularly characterized using primers targeting the Rickettsia gltA gene, whose sequence matched 100% the corresponding sequences of R. bellii. Seroprevalence against SFG rickettsiae in sampled dogs (n=83) was 41% or 57%, depending on the rickettsial antigen (R. rickettsii strain Taiaçu or R. parkeri strain Atlantic rainforest, respectively). A total of 37 (45%) canine sera showed titers to R. parkeri at least fourfold higher than to R. rickettsii antigen. Among humans, 10% (4/41) of the samples reacted to at least one rickettsial antigen, with the highest endpoint titer varying from 64 to 128 for R. rickettsii and R. parkeri. No human serum showed ≥4-fold difference between the highest endpoint titers. Finally, during the study period, suspicions on cases of R. parkeri rickettsiosis were not informed by the health secretariats. Our results confirm the presence and exposure to R. parkeri strain Atlantic rainforest, associated with two anthropophilic tick species (A. ovale and A. aureolatum) parasitizing domestic dogs with unrestrained access to forest areas. Consequently, the occurrence of R. parkeri infection in humans inhabiting the Atlantic forests of ES should not be discarded.